The T﻿urkish Version of the Revised Nottingham Sensory Assessment: Validity and Reliability in Chronic Stroke Survivors - Bilgin, Nurten; Akyurek, Gokcen (Cognitive and behavioral neurology, 2025)
Evaluation of sensory functions in chronic stroke survivors is essential to plan and implement effective treatment and rehabilitation. To investigate the validity and reliability of the Turkish version of the Revised Nottingham Sensory Assessment (rNSA-T) in chronic stroke survivors. We applied the World Health Organization's translation protocols to develop the rNAS-T. We then tested its validity and reliability in 85 chronic stroke survivors using criterion validity and consistency for demographic variables, as well as﻿ test-retest and inter-rater reliability analyses﻿. The criterion validity of the rNSA-T was supported by significant correlation between participants' scores on the rNSA-T, the Katz Index of Independence in Activities of Daily Living (Katz-AD) ( r = 0.430-0.674, P < 0.05), and the Rivermead Motor Assessment (RMA) ( r = 0.528-0.773, P < 0.05). rNSA-T results remained consistent across variables of sex and side affected by stroke ( P > 0.05). The test-retest reliability of the rNSA-T was excellent in all subdimensions (ICC = 0.865-1.000), as was the inter-rater reliability (κ = 0.875-1.000). The rNSA-T is a valid and reliable tool for evaluation of sensory functions in chronic stroke survivors.